2015
DOI: 10.5713/ajas.15.0627
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fermentation in Improving Nutritional Quality of Soybean Meal — A Review

Abstract: Soybean meal (SBM), a commonly used protein source for animal feed, contains anti-nutritional factors such as trypsin inhibitor, phytate, oligosaccharides among others, which limit its utilization. Microbial fermentation using bacteria or fungi has the capability to improve nutritional value of SBM by altering the native composition. Both submerged and solid state fermentation processes can be used for this purpose. Bacterial and fungal fermentations result in degradation of various anti-nutritional factors, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
168
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(182 citation statements)
references
References 35 publications
8
168
2
4
Order By: Relevance
“…The results showed the improved growth performance, consistent with other studies (Jones et al, 2010). Fermentation improved the bioavailability of nutrients, because of the increase in soluble protein and small peptide content, and the effective removal of anti-nutritional factors in soybean meal after fermentation (Mukherjee et al, 2016). Canibe and Jensen (2003) reported that fermented liquid feed could reduce the quantity of gastrointestinal pathogens in growing pigs, maintain intestinal health, and then improve growth performance of pigs compared with dry feed.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results showed the improved growth performance, consistent with other studies (Jones et al, 2010). Fermentation improved the bioavailability of nutrients, because of the increase in soluble protein and small peptide content, and the effective removal of anti-nutritional factors in soybean meal after fermentation (Mukherjee et al, 2016). Canibe and Jensen (2003) reported that fermented liquid feed could reduce the quantity of gastrointestinal pathogens in growing pigs, maintain intestinal health, and then improve growth performance of pigs compared with dry feed.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, the reduction of NH 3 emissions was due to fresh fermentation of soybean meal. Mukherjee et al (2016) have shown that fresh FSM contained a high proportion of small peptides and digestive enzymes, improving nutritional quality of soybean meal, increasing the utilization of dietary nitrogen, and thereby reducing the emissions of nitrogenous substances in livestock. Hobbs et al (1997) reported that feeding wet material could promote protein digestion and absorption, and then reduce nitrogen emissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also confirmed the availability of nutrients and degradation of anti-nutritive compounds during the fermentation of soybean [16].…”
Section: Proximate Analysismentioning
confidence: 85%
“…The potential feed stuffs as sources of protein are soybean meals and soybean wastes. Soybean meal (SBM) is the remained material after the extraction of oil from SB flakes, with about 48% crude protein (CP) content (Mukherjee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%